PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN AUDIOVISUAL TERHADAP MINAT BELAJAR PESERTA DIDIK PIANO DI HARDMAN MUSIC COURSE - Yodie Florentio Azhar; Riyan Hidayatullah (STKIP Pesisir Selatan, 2026)
Formal education aims to provide a strong foundation for students by providing knowledge, skills, and attitudes that are relevant to the development needs of individuals and society. Through education, individuals can be shaped into individuals with extensive knowledge, adequate skills, and strong character. Through the educational process, a person is equipped not only with intellectual abilities but also with the moral values, attitudes, and ethics necessary for social life. The purpose of this study is to obtain information on how the use of audiovisual learning media can enhance students' motivation in piano lessons. This media is used as a means to present piano material in a more engaging way through a combination of sound and visual elements, which helps students understand the material more clearly. To describe the process and effects of using learning media, this study employs a qualitative and descriptive methodology. The research shows that audiovisual learning media can increase students’ interest in learning, as indicated by improved attention, motivation, and active participation during the learning process. Therefore, audiovisual media can be used as an effective alternative for teaching piano and supporting the achievement of learning objectives.